Information literacy training for teenager-students of Islamic boarding school on the digital era - Mochammad Sa'id; Raisyah Ayu R.A. Arsad; Rikza Fitrotul Umaroh; Rakhmaditya Dewi Noorrizki; Angga Yuni Mantara (University of Merdeka Malang, 2022)
The industrial revolution makes an impact on social change, especially with the presence of social media, which then accelerates the dissemination of information. However, because of the large amount of information that is spread in cyberspace, not all information is filtered properly and often results in the emergence of false information (hoax). In order to overcome these problems, each people must have information literacy skills, including adolescent students of boarding school. To improve the knowledge and information literacy skills of adolescent students of boarding schools in the digital era, we held training on information literacy. The training was held at Al-Amin Islamic Boarding School Mojokerto for 2 days. The participants were 70 male students of classes X and XI at Al-Amin Islamic Boarding High School Mojokerto. The training was carried out in 4 stages, namely, pretest, information literacy material, opinion article writing material, and posttest. Based on the difference test, the average value of the pretest was 78.63 and the post-test was 87.02. While the Paired Sample T-Test obtained a value of 0.000 0.05. This shows that there is a significant difference in the information literacy skills of participants before and after the training. Thus, conclusively, the training in information literacy can improve the information literacy skills of adolescent students at Al-Amin Islamic Boarding High School Mojokerto.